1998
DOI: 10.1074/jbc.273.17.10091
|View full text |Cite
|
Sign up to set email alerts
|

ATP Binding Induces Large Conformational Changes in the Apical and Equatorial Domains of the Eukaryotic Chaperonin Containing TCP-1 Complex

Abstract: The chaperonin-containing TCP-1 complex (CCT) is a heteromeric particle composed of eight different subunits arranged in two back-to-back 8-fold pseudo-symmetric rings. The structural and functional implications of nucleotide binding to the CCT complex was addressed by electron microscopy and image processing. Whereas ADP binding to CCT does not reveal major conformational differences when compared with nucleotide-free CCT, ATP binding induces large conformational changes in the apical and equatorial domains, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 36 publications
3
40
0
Order By: Relevance
“…2 Third, the conformations in the nucleotide-free state and the ADP-bound state are the same or very similar to each other. This is consistent with previous results of electron microscopy and small angle neutron scattering measurement showing that the binding of ADP does not induce a major change in structure among group II chaperonins (12)(13)(14)29). Melki et al (30) pointed out that there are large differences between ADPAlF 4 Ϫ -CCT, corresponding to the state of transition of ATP hydrolysis, and ADP-CCT in electron microscopic images and hydrodynamic properties.…”
Section: Model Of the Functional Cycle Of T Ks-1 ␣ Subunit Chaperonin-supporting
confidence: 81%
See 1 more Smart Citation
“…2 Third, the conformations in the nucleotide-free state and the ADP-bound state are the same or very similar to each other. This is consistent with previous results of electron microscopy and small angle neutron scattering measurement showing that the binding of ADP does not induce a major change in structure among group II chaperonins (12)(13)(14)29). Melki et al (30) pointed out that there are large differences between ADPAlF 4 Ϫ -CCT, corresponding to the state of transition of ATP hydrolysis, and ADP-CCT in electron microscopic images and hydrodynamic properties.…”
Section: Model Of the Functional Cycle Of T Ks-1 ␣ Subunit Chaperonin-supporting
confidence: 81%
“…On the other hand, Llorca et al (11) showed that the binding of AMP-PNP to CCT results in the cavity being closed off by the helical protrusions of the apical domains. Also, they showed that ATP induces an asymmetric structure; one of the rings in the conformation is similar to that of the nucleotide-free CCT, whereas the other presents a more open conformation (12,13). Gutsche and colleagues (14) pointed out that the binding of ATP or AMP-PNP to the thermosome induces the closed conformation.…”
mentioning
confidence: 99%
“…The functional cycle of group II chaperonins is therefore likely to be more different from that of group I chaperonins than previously supposed (27). A mechanistic difference between the two chaperonin types is also indicated by the recent electron microscopy study of Llorca et al (31), which revealed very extensive loosening of both intra-and inter-ring contacts between subunits in just one of the two CCT rings upon binding of ATP or the non-hydrolyzable analog, AMP-PNP. No equivalent opening out occurs in GroEL upon ATP binding, but rather, large movements about hinge regions in the intermediate domain result in the movements of substrate binding sites on the apical domain up and away from the central cavity (3).…”
mentioning
confidence: 69%
“…Availability of pure components will also be required for an electron microscopic study of K ϩ -ATP-induced CCT disassembly. From the report of Llorca et al (31), we know at present that ATP, like AMP-PNP, binding to CCT causes extensive opening out of subunits within one of the two chaperonin rings, but since these specimens were prepared in the absence of K ϩ ions, structural changes consequent to ATP hydrolysis and the presence of the additional disassembly factor(s) could not have been observed. An electron microscopic examination will be particularly informative also because some idea of the time scale of the disassembly process will be obtained.…”
Section: Atp-dependent Disassembly Of the Cct Chaperoninmentioning
confidence: 99%
See 1 more Smart Citation